iTRAQ-Based Quantitative Proteomic Profiling of Staphylococcus aureus Under Different Osmotic Stress Conditions - Ming, Tinghong; Geng, Lingxin; Feng, Ying; Lu, Chenyang; Zhou, Jun; Li, Yanyan; Zhang, Dijun; He, Shan; Li, Ye; Cheong, Lingzhi; Su, Xiurong (Frontiers in Microbiology, 2019)
Staphylococcus aureus (S. aureus) is an extremely halotolerant pathogenic bacterium with high osmotic stress tolerance, and it is frequently encountered in aquatic production and preservation. However, the mechanism underlying the extremely high osmotic stress tolerance of S. aureus remains unclear. In this study, the isobaric tags for relative and absolute quantification (iTRAQ) method was used to identify the differentially expressed proteins (DEPs) under different sodium chloride (NaCl) concentrations. Compared with the control group (0% NaCl), the 10% and 20% NaCl groups had 484 DEPs and 750 DEPs, respectively. Compared with the 10% NaCl group, the 20% NaCl group had 361 DEPs. Among the DEPs, proteins involved in fatty acid synthesis, proline/glycine betaine biosynthesis and transportation, stress tolerance, cell wall biosynthesis and the TCA cycle were upregulated, whereas proteins associated with biofilm formation and pathogenic infections were downregulated. The results obtained in this study indicate that under extremely high osmotic stress, modification of the cell membrane structure, increased biosynthesis and transportation of osmotic protectants, and redistribution of energy metabolism contribute to the osmotic stress tolerance of S. aureus, and the infectious ability of the bacteria may be limited. The aim of this study was to provide new insight into how S. aureus tolerates the high-salt conditions involved in aquatic production and preservation.